2020
DOI: 10.1097/ipc.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Outbreak in a Veterans Affairs Long-term Care Facility

Abstract: Background Respiratory syncytial virus (RSV) is increasingly becoming an important cause of respiratory infections in adults, especially those living in long-term care facilities (LTCFs). Seasonal outbreaks peaking from October to April are common. We report an outbreak of RSV involving 2 LTCFs with total capacity of 80 beds in 2019. Methods Retrospective chart review of cases identified with positive RSV infection via DNA polymerase chain reaction (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Studies were published between 18 April 2000 and 1 March 2023. Of the 20 included studies, nine were conducted in the USA [17][18][19][20][21][22][23][24][25], two in Canada [26,27], one each in Japan [28], Netherlands [29], England [30], Czech Republic [31], Portugal [32], Hong Kong [33], France [34], Slovenia [35], and one multi-country (Belgium, Estonia, Germany, Spain, United Kingdom and USA) [6].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies were published between 18 April 2000 and 1 March 2023. Of the 20 included studies, nine were conducted in the USA [17][18][19][20][21][22][23][24][25], two in Canada [26,27], one each in Japan [28], Netherlands [29], England [30], Czech Republic [31], Portugal [32], Hong Kong [33], France [34], Slovenia [35], and one multi-country (Belgium, Estonia, Germany, Spain, United Kingdom and USA) [6].…”
Section: Resultsmentioning
confidence: 99%
“…Overall case fatality rate ranged from 7.7-23.1% [17,19,[30][31][32][33] (Table 2). Only one study reported populationbased mortality rates [21].…”
Section: Rsv-associated Case Fatalitymentioning
confidence: 99%
See 3 more Smart Citations